The Influence of Brand Image, E-WOM, and Customer Rating on Purchase Decisions on Shopee E-Commerce - Vani Zahara Maulidya; Mas Oetarjo; M. Rizal Yulianto (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The advancement of information and communication technology has had a significant impact on its users. This has intensified competition in the business world, and technological developments continue to strengthen the e-commerce industry. This study aims to examine the effect of brand image, e-WOM, and customer ratings on purchasing decisions in Shopee e-commerce. A quantitative approach was employed, using a non-probability sampling technique with the axial sampling method, involving 96 respondents. Data was collected through questionnaires distributed via Google Forms. The study's findings indicate that brand image has a positive and significant influence on purchasing decisions in online shopping through Shopee. Similarly, the e-WOM (electronic word-of-mouth) variable also exerts a positive and significant impact on purchasing decisions. Customer ratings further contribute positively and significantly to purchasing decisions on Shopee e-commerce. These findings highlight the crucial role of brand perception, online consumer reviews, and ratings in shaping purchasing behavior in e-commerce. Business actors on Shopee can leverage these factors to enhance their marketing strategies and build consumer trust.